2012
DOI: 10.1148/radiol.11102289
|View full text |Cite
|
Sign up to set email alerts
|

No Benefit for Consensus Double Reading at Baseline Screening for Lung Cancer with the Use of Semiautomated Volumetry Software

Abstract: Purpose:To retrospectively evaluate the performance of consensus double reading compared with single reading at baseline screening of a lung cancer computed tomography (CT) screening trial. Materials and Methods:The study was approved by the Dutch Minister of Health and ethical committees. Written informed consent was obtained from all participants. The benefi t of consensus double reading was expressed by the percentage change in cancer detection rate, recall rate, number of additional nodules detected, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…For example, in the NELSON trial, each participant was assessed twice in the central and the local site. Two radiologists with more than 6 years' experience performed the evaluation in the central site, and 13 radiologists or residents with variable experiences in the local sites [30]. To closely simulate this clinical practice, we chose one observer for the first round of measurement and two observers for the second measurement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the NELSON trial, each participant was assessed twice in the central and the local site. Two radiologists with more than 6 years' experience performed the evaluation in the central site, and 13 radiologists or residents with variable experiences in the local sites [30]. To closely simulate this clinical practice, we chose one observer for the first round of measurement and two observers for the second measurement.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of acquisition (2005), all CT images of the lungs from each examination were independently read by first and second readers (double reading) as part of the NELSON protocol [6, 23]. The first reading was performed by 13 readers (experience in reading thoracic CT varying from 0 to 20 years); the second reading was performed by two readers, each with 6 years of experience.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the number of missed lesions, double reading has been recommended [5]. Previous studies have found that more pulmonary nodules are detected by double reading than by single reading [5, 6]. However, double reading is not widely used in clinical routine because of limited human resources and cost-effectiveness [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these fi ndings, the fourth screening round image reading in the Dutch-Belgian randomized lung cancer screening trial (NELSON ) is, in fact, performed by only one reader. 6 With the recent grade B recommendation by the US Preventive Task Force for lung cancer screening using low-dose CT imaging, the incidence of pulmonary nodules has the potential to rise dramatically. Because the majority of these nodules are not cancer, volumebased nodule management has been suggested to be more accurate than diameter measurements, with signifi cantly lower false-positive rates.…”
Section: Responsementioning
confidence: 99%